2021
DOI: 10.3390/ma14164676
|View full text |Cite
|
Sign up to set email alerts
|

An Engineering Zirconia Ceramic Made of Baddeleyite

Abstract: Wet high-energy milling and uniaxial pressing are used to fabricate CaO-stabilized tetragonal zirconia polycrystalline ceramic (Ca-TZP) with decent mechanical characteristics, i.e., a hardness of 11.5 GPa, Young’s modulus of 230 GPa, and fracture toughness of 13 MPa·m0.5. The effect of CaO concentration and the sintering temperature on phase composition and mechanical characteristics of CaO-stabilized zirconia ceramic made of baddeleyite is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It seems that the last is about 1 µm for ceramics of this type. According to [58], the microhardness of m-ZrO 2 is lower than t-ZrO 2 . During indentation, the t-m transition occurs with the formation of m-ZrO 2 which causes the lowering of microhardness.…”
Section: Mechanical Properties Of Ysz Ceramics and The Relations To T...mentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the last is about 1 µm for ceramics of this type. According to [58], the microhardness of m-ZrO 2 is lower than t-ZrO 2 . During indentation, the t-m transition occurs with the formation of m-ZrO 2 which causes the lowering of microhardness.…”
Section: Mechanical Properties Of Ysz Ceramics and The Relations To T...mentioning
confidence: 99%
“…In particular, from the point of view of yttrium distribution between the t-ZrO 2 and m-ZrO 2 phases (Table 2), a steep decrease in yttrium percentage was observed for the m-ZrO 2 phase agglomerates with a sintering temperature increase. However, this did not allow the (t-m) ZrO 2 phase transformation [58] to occur to a great extent and thus did not provide high values of fracture toughness even for variant 8YSZ-1600. The morphology of the m-ZrO 2 phase agglomerates was characterized by blurred contours and the t-ZrO 2 phase particles were quite distinct for variant 8YSZ-1550 (Figure 7g).…”
Section: Mechanical Properties Of Ysz Ceramics and The Relations To T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chu Liang and Chang Zhisheng [22] [23] conducted acoustic emission signal monitoring on the Brazilian splitting test process of zirconia toughened alu-mina, and found that zirconia toughened alumina ceramics have higher fracture tough-ness compared to alumina ceramics without toughening effect. Scholars have also con-ducted relevant studies on the fracture toughness of zirconia ceramics under different conditions [24] [25] [26] [27]. When studying the deformation and damage of zirconia ceramics, many cracks are excited.…”
Section: Introductionmentioning
confidence: 99%
“…This transformation, related with a volumetric expansion about 4-5%, contributes to the decrease in zirconia-based ceramics implant strength. Different types of oxides are used as stabilizers (such as Y2O3, MgO and others) to maintain the appropriate tetragonal phase at room temperature (Rodaev et al, 2019).…”
Section: Introductionmentioning
confidence: 99%